Strategi Penyelenggaraan Praktikum dan Pengelolaan Laboratorium Pendidikan di Program Studi Sarjana Teknik Elektro - Muhammad Amin Sulthoni (Universitas Pendidikan Indonesia, 2021)
This paper describes various strategies and tactical steps that are applied in managing educational laboratories that must manage a large capacity practicum effectively and efficiently, while maintaining good quality. This study uses a descriptive approach to study the quality of the implementation and management of practicum at LDTE which is characterized by the perceptions and assessments of practicum and staff. Surveys from student participants show that the laboratory and practicum management at LDTE has gone well and satisfactorily. Every semester, Basic Laboratory of Electrical Engineering (LDTE), School of Electrical and Informatics Engineering, Bandung Institute of Technology is targeted to serve around 370 students from three study programs who take an average of two practicum subjects from the seven practicum subjects held.